Back Cover: Investigation of NV centers in diamond nanocrystallites and nanopillars (Phys. Status Solidi B 1/2013). Issue 1 (8th January 2013) - Petkov, Emil; Popov, Cyril; Rendler, Torsten; Petkov, Christo; Schnabel, Florian; Fedder, Helmut; Lee, Sang‐Yun; Kulisch, Wilhelm; Reithmaier, Johann Peter; Wrachtrup, Jörg
<x xml:space="preserve">Abstract</x> Color defects in diamond and especially nitrogen‐vacancy (NV) centers attract an ever increasing scientific interest due to their spin‐controlled properties as a result of which applications in quantum information technology and magnetometry of single spins can be envisioned. The enhancement of the photon emission from NV centers and the collection efficiency rely on their incorporation in optical structures, like photonic crystals, nanopillars, microrings, etc. Petkov et al. (pp. 48–50) investigated NV centers incorporated during hot filament chemical vapor deposition of diamond nanocrystallites and nanocrystalline diamond (NCD) films. From the latter nanopillars with different diameters were prepared applying electron beam lithography (EBL) and inductively coupled plasma reactive ion etching (ICP‐RIE) with oxygen. The deposition of either single crystallites or closed films was controlled by the nucleation density on the silicon substrates and the process duration. Optical investigations revealed the presence of ensembles of color centers in both nanostructures. An enhancement of the fluorescence emission by an order of magnitude was observed after the structuring of the NCD films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>